Modelling of rainfall-runoff relationship at subcatchment of Universiti Malaysia Pahang, Gambang Campus - Siti Hajar, Rosli (2016)
Universiti Malaysia Pahang (UMP) has drainage system that is insufficient to cattle the capacity of the runoff especially in Block W due to urbanization. Drainage design in UMP not take account the future development so, it’s not able to function properly. Before this, drainage system in UMP is design for the Malaysia Electrical Corporation’s (MEC) factory. Based on “Manual Saliran Mesra Alam” (MASMA) the design of minor drainage is for five years Average Recurrence Interval (ARI). Due to that design year, UMP exposed to serious flash flood. Therefore, this study is to determine the rainfall-runoff relationship, analyse rainfall-runoff data using Snyder and Clark method in HEC-HMS computer program. The study area is the drainage system with 0.11 slopes of UMP surrounding laboratories, Block W and new buildings with 0.8 m2. From this study, it was found that runoff is depending on the rainfall intensity. Using HEC-HMS gave satisfying results and it is suitable for simulating future urbanization. In this software, hydrology parameter such as loss rate, transform and base flow are important to simulate the data. However, it is difficult to obtain accurate and suitable parameters for a catchment area. Nine storm event were used for calibration in order to get an optimum values for catchment area of UMP. After the comparison between Snyder and Clark Time Area method, Snyder method is the best method for UMP area with the Efficiency Index of 75.09%.